Servant Leadership, Innovative Capacity and Performance in Third Sector Entities - Hernández-Perlines, Felipe; Araya-Castillo, Luis Andrés (Frontiers in Psychology, 2020)
This paper analyses the relationship between servant leadership, innovative capacity and performance in Third Sector entities and proposes a mediation model. This research is based on a two-fold theoretical approach: the servant leadership approach and the resource-based approach. The data have been obtained through a survey sent to territorial and functional managers of Third Sector entities. The fieldwork ran from June to September 2019. At the end of the entire process, 85 valid questionnaires were obtained. For the analysis of the results, a double methodology has been used: (1) a method of second order structural equations (PLS-SEM) and, (2) qualitative comparative analysis (QCA). The main contributions of this work are: 1) a double theoretical approach has been applied in this work, which has allowed to adequately define the relationships between servant leadership, innovation capacity and performance in Third Sector entities; (2) the application of a double data analysis methodology has allowed us to obtain robust and reliable results; (3) the measures of the three composites used (servant leadership, innovative capacity and performance) have adequate reliability and validity values; (4) the servant leadership positively influences the performance of Third Sector entities being able to explain the 35.6% of the variation of the performance of these entities and besides, it is a necessary condition for this performance to take place, (5) the average innovative capacity in the influence of the servant leadership in the performance of the entities of the Third Sector, being a necessary condition. Mediation is total, eliminating the direct effect of servant leadership on the performance of third Sector entities and increasing the capacity to explain the variation in the performance of Third Sector entities up to 44.7%.